2022
DOI: 10.3390/pharmaceutics14050920
|View full text |Cite
|
Sign up to set email alerts
|

Single-Step Self-Assembly of Zein–Honey–Chitosan Nanoparticles for Hydrophilic Drug Incorporation by Flash Nanoprecipitation

Abstract: Zein- and chitosan-based nanoparticles have been described as promising carrier systems for food, biomedical and pharmaceutical applications. However, the manufacture of size-controlled zein and chitosan particles is challenging. In this study, an adapted anti-solvent nanoprecipitation method was developed. The effects of the concentration of zein and chitosan and the pH of the collection solution on the properties of the zein–honey–chitosan nanoparticles were investigated. Flash nanoprecipitation was demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Additionally, Xu et al, reported low EE of CPX in PLA-DEX NPs (1.1 ± 0.04% (CPX at 4 mg/mL) and a mass loading of 8.45 ± 0.31%) in PLGA-PEG NPs the EE was 1.35 ± 0.07% with a loading of 10.79 ± 0.59% [ 79 ]. Furthermore, the encapsulation of other lipophilic compounds into zein NPs is comprehended between 47.80 and 98% [ 18 , 24 , 80 , 81 , 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Xu et al, reported low EE of CPX in PLA-DEX NPs (1.1 ± 0.04% (CPX at 4 mg/mL) and a mass loading of 8.45 ± 0.31%) in PLGA-PEG NPs the EE was 1.35 ± 0.07% with a loading of 10.79 ± 0.59% [ 79 ]. Furthermore, the encapsulation of other lipophilic compounds into zein NPs is comprehended between 47.80 and 98% [ 18 , 24 , 80 , 81 , 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, flash nanoprecipitation (FNP) is a simple and effective approach to producing NPs with high drug-encapsulation efficiency (EE) [ 16 ]. The FNP technique is based on a rapid mixing that creates high-supersaturation conditions, leading to the precipitation and encapsulation of both hydrophobic and hydrophilic drugs into polymeric NPs [ 16 , 17 , 18 ]. Several studies demonstrated that FNP allows the encapsulation of hydrophobic and hydrophilic drugs with high EE, as we have previously reported [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors affecting the bioclearance rate of agents include size, surface modification, and charge. For example, the circulating time of nanoparticles (NPs) in blood can be prolonged by reducing the size and achieving homogeneous distribution in tissues . Moreover, previous studies suggested that NPs with a diameter less than 10 nm are most likely to be rapidly cleared by the kidneys .…”
Section: Principles Of Pai and Applications For Cancer Theragnosticsmentioning
confidence: 99%
“…For example, the circulating time of nanoparticles (NPs) in blood can be prolonged by reducing the size and achieving homogeneous distribution in tissues. 84 Moreover, previous studies suggested that NPs with a diameter less than 10 nm are most likely to be rapidly cleared by the kidneys. 85 Furthermore, previous research results reveal that the clearance rate depends on the surface medication via affecting their physicochemical properties.…”
Section: Principles Of Pai and Applications For Cancer Theragnosticsmentioning
confidence: 99%